Ontogenia, filogenia y el origen de la diversidad floral en el complejo de ponthieva (orchidaceae, cranichidinae) - Rizo Patrón Viale, Federico Luis Sebastián (2013)
Federico Rizo Patrón Viale. Ontogenia, Filogenia y El Origen de la Diversidad Floral en el Complejo de Ponthieva (Orchidaceae, Cranichidinae). Advisor: Dr. José Mostacero León. 58 pages. Year: 2013. Institutions: Trujillo National University and the Biology Institute from the National Autonomous University of Mexico. Floral diversity can be given by the adaptation of plant species to different ecological characteristics. Phylogenetic analysis found that in the Cranichidinae subtribe, species from different genera were interspersed, making a polyphyletic group. This thesis pursue to know floral ontogenic characteristics of Ponthieva fertilis and Cranichis elliptica and post anthesis morphological characteristics from ten species from this group to compare them with other members of the subtribe. Also to know homologies and differences between species. Specimens from four species were collected in Junín and Pasco Regions. Collection specimens from the MEXU herbarium were used. Flowers in anthesis from Ponthieva fertilis and Cranichis elliptica were dissected to analyze floral characteristics and were observed with scanning electron microscopy for ontogenic analysis. Transverse anatomic sections from anthesis flowers of P. fertilis were done to observe the sequence of vascular bundles. Homologies between species of Cranichidinae were found and could be used in classification. Floral parts from different species showed characteristics that suggest an evolutionary relationship with pollinators. P. fertilis and Cranichis elliptica have the same initiation sequence from the floral parts and differences come out at late stages of preantesis. Conclusions are: Cranichidinae subtribe could have a wide range of pollinators. This subtribe constitutes a basal group in orchid phylogeny based in its anatomical characteristics. Main differences between P. fertilis y C. elliptica are perianth shape and the rostellum. No evidence was found for the existence of rudimentary staminodes. For a strong classification, morphological characters should be complemented with molecular characters.